Teaching accelerated nursing students' self‐care: A pilot project - Cheryl Green (Wiley, 2020)
Abstract Aim A benchmark of 4 has been determined for the reduction of self‐reported stress by nursing students' status post 5 weeks of holistic educational activities and interventions provided by a nurse educator. Design Provision 5 in the American Nurses Association Code of Ethics for Nurses with Interpretive Statements emphasizes the duty of the nurse to not only promote the health and safety of others, but to self as well (ANA, 2015, Code of ethics with interpretive statements, Nursebooks.org). A self‐care for nurses' pilot project was trialled with 25 accelerated nursing students over the course of 5 weeks. Holistic education programmes were facilitated by a nurse educator uninvolved in providing clinical or classroom education to the students. Methods The Standards for Quality Improvement Reporting Excellence (SQUIRE) guidelines are used in this pilot project as a framework to explore standardization of education of nursing students about self‐care in nursing programmes and to promote positive health behaviours and student nurses' insight into how nurses' self‐care can have an impact on patient outcomes. The self‐care pilot project introduced the importance of self‐care for the pre‐licensure nursing student by teaching healthy eating, physical exercise, the value of sleep, use of positive affirmations and aromatherapy to a cohort of accelerated nursing students over the course of 5 weeks. The Star Model of Knowledge Transformation was the theoretical framework for the pilot study. Two questionnaires were used by the principal investigator to obtain participant data, the Project Participant Questionnaire and the Final‐Year Group Questionnaire. Results On completion of the self‐care for nurses' pilot, the nursing students reported a reduction in stress and an increased ability to cope with stress after exposure to different holistic stress reduction strategies. An average benchmark of 4.36 was achieved indicating that the nursing students' self‐care had improved status post the interactive teaching intervention. Self‐care taught to pre‐licensure nursing students by nurse educators can enhance their self‐awareness of the importance of stress reduction and care of themselves while enduring the academic rigour and simultaneous clinical practicum experiences in nursing programmes. Applying self‐care behaviours to reduction of stress for nursing students may be of benefit to of students as they transition from the pre‐licensure to graduate nurse roles. Hence, teaching health behaviours that are self‐protective and contribute to maintaining safe clinical environments for nurses and the patients in their care.